Relationship between superoxide dismutase and pathogenic mechanisms of Listeria monocytogenes. - Welch, D F (1979)
Listeria monocytogenes was examined for superoxide dismutase(SOD) activity. Two catalase-negative strains possessed at least twofold greater SOD activities than the catalase-positive L. monocytogenes strains examined. Growth conditions such as aeration and iron concentration influenced the specific activity of SOD obtained from cells cultured in defined media. L. monocytogenes SOD from crude extracts and after partial purification was analyzed by polyacrylamide gel electrophoresis. Iron was associated with the single band of SOD activity detected in the gels. SOD activity appeared to be primarily extracytoplasmic. Survival of organisms in a superoxide-generating medium was studied, with photoactivation of riboflavin used as the source of free radical formation. Virulent, catalase-positive L. monocytogenes strains were relatively resistant to killing in a pH 7 superoxide-containing medium. An intact-cell assay for SOD was developed, which used the superoxide-generating system and employed the superoxide-dependent oxidation of sulfite, added to the medium, and inhibition of this oxidation by SOD. Maximal SOD activites of intact cells were observed when 100 to 400 micrograms (dry weight) of viable Listeria cells per ml was added to the medium. A possible role for SOD in the pathogenesis of listeric infection is discussed.